Downregulation of Neuronal and Dendritic Connexin36-Made Electrical Synapses Without Glutamatergic Axon Terminals in Spinal Anterior Horn Cells From the Early Stage of Amyotrophic Lateral Sclerosis - Kobayakawa, Yuko; Masaki, Katsuhisa; Yamasaki, Ryo; Shiraishi, Wataru; Hayashida, Shotaro; Hayashi, Shintaro; Okamoto, Koichi; Matsushita, Takuya; Kira, Jun-ichi (Frontiers in Neuroscience, 2018)
Connexin36 (Cx36) forms gap junctions between neurons, which are called electrical synapses, enabling adjacent neurons to communicate directly. The participation of chemical synapses in neurodegeneration in amyotrophic lateral sclerosis (ALS) has long been indicated, but it remains unclear whether electrical synapses are involved in the pathogenesis of ALS. We performed extensive immunopathological analyses using mutant superoxide dismutase 1 (SOD1G93A) transgenic mice and their littermates to investigate whether Cx36-made electrical synapses are affected in motor neuron diseases. We found that in the lamina IX of the lumbar spinal cord from wild type mice, about half of the Cx36 puncta existed independently of chemical synapse markers, while the rest coexisted with chemical synapse markers such as vesicular glutamate transporter 1 (VGLUT1), which is a glutamatergic axon terminal marker, and/or glutamate decarboxylase 65 (GAD65), which is a GABAergic axon terminal marker. Cx36 single or Cx36/GAD65 double positive puncta, but not VGLUT1-containing puncta, were preferentially decreased on neuronal and dendritic surfaces of the anterior horn cells in the early stage of SOD1G93A ALS mice. Moreover, in five human autopsied sporadic ALS cases with bulbar or upper limb onset, Cx36 immunoreactivity was diminished in the proximal dendrites and neuropils of well-preserved large motor neurons in the lumbar anterior horns. These findings suggest that downregulation of neuronal and dendritic Cx36 in the spinal anterior horns commonly occurs from the early stage of hereditary and sporadic ALS. Cx36-made electrical synapses without glutamatergic signaling appear to be more vulnerable than other chemical synapses and electrical synapses with glutamatergic signaling in the early stage of motor neuron degeneration, suggesting involvement of Cx36-made electrical synapses in the pathogenesis of human ALS.